2018
DOI: 10.1016/j.matdes.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The brittle-ductile transition of tungsten single crystals at the micro-scale

Abstract: The loading rate effect on the brittle-ductile transition temperatures of tungsten single crystals at the micro-scale was investigated by microcantilevers with a (100)[001] crack system. Specimens with a length to width to height of 15 µm / 4 µm / 6 µm were fabricated by focused ion beam milling. At low temperatures (-90 to -25 °C) the samples failed by brittle cleavage fracture, irrespective of the applied loading rate at a fracture toughness of 3.2 MPa•m 1/2 . With increasing temperatures up to 500 °C and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 67 publications
4
34
3
1
Order By: Relevance
“…However, it is evident that a BDT begins somewhere below 125°C, where in bulk W, plasticity begins to be enhanced. This is in relative agreement with the literature regarding the BDTT of bulk single crystals of tungsten; Gumbsch et al [31] found the BDTT of tungsten single crystals to depend on both crack plane and crack front direction, ranging from 370-470 K. The BDT also is not a sharp transition, as shown by both Gumbsch for macroscale crystal fracture and Ast et al [39] for fracture of microcantilevers oriented for fracture along the {100}<010> crack system. In addition, 3DOM W is polycrystalline; some averaging of the BDTT across crack systems is to be expected.…”
Section: Frustum Indentation Of 3dom Wsupporting
confidence: 88%
“…However, it is evident that a BDT begins somewhere below 125°C, where in bulk W, plasticity begins to be enhanced. This is in relative agreement with the literature regarding the BDTT of bulk single crystals of tungsten; Gumbsch et al [31] found the BDTT of tungsten single crystals to depend on both crack plane and crack front direction, ranging from 370-470 K. The BDT also is not a sharp transition, as shown by both Gumbsch for macroscale crystal fracture and Ast et al [39] for fracture of microcantilevers oriented for fracture along the {100}<010> crack system. In addition, 3DOM W is polycrystalline; some averaging of the BDTT across crack systems is to be expected.…”
Section: Frustum Indentation Of 3dom Wsupporting
confidence: 88%
“…Описанные методы и приемы опробованы и использовались на макрооднородных монокристаллических, аморфных, композитных материалах, высокоэнтропийных и интерметаллических сплавах [119,163,164], пленочных керамических покрытиях (как для определения их собственных свойств, так и энергии адгезии к подложке) [193][194][195]. В [196][197][198] этими методами определяли условия перехода от вязкого к хрупкому разрушению (в частности, температуру и размеры пластической зоны в вершине трещины), а в [199] -закономерности водородного охрупчивания.…”
Section: разрушение в микро- субмикрои наношкалеunclassified
“…[18,20]: filled square: single-crystalline; open square: polycrystalline hot-deformed; crossed square: polycrystalline assintered; Ref. [19]: half-filled square (bottom filled): singlecrystalline; Refs. [17,82]: half-filled square (top filled): singlecrystalline; Ref.…”
Section: Evolution Of Bdt Arrhenius Activation Energiesmentioning
confidence: 99%
“…Experiments using the model material tungsten (W) [16] have suggested that the glide of dislocations controls the BDT [17]. For W this has been validated and specified to the glide of h111i screw dislocations by studies performed on single crystals on the macroscale [18] and microscale [19], on a hot-deformed fine-grained [20], on coarsegrained recrystallized microstructures [21], and on hot-deformed materials that have undergone at least partial recrystallization [20,22].…”
Section: Introductionmentioning
confidence: 99%